Aggregatibacter actinomycetemcomitans modulates toll-like receptors 2 and 4 in gingival epithelial cells in experimental periodontitis - Mythily Srinivasan; Krithika N Kodumudi; Dominique M Galli (Wolters Kluwer Medknow Publications, 2010)
Background: Periodontitis is a common bacterial infection precipitated by exaggerated host responses to the oral microorganisms, As the first cells to encounter the oral pathogens the gingival epithelial cells (GEC) respond via toll-like receptors (TLR) that recognize conserved microbial patterns. Here we investigated the expression of TLR-2 and TLR-4 in GEC of naοve mice in response to infection with the periodontal pathogen Aggregatibacter actinomycetemcomitans (Aa). Methods: 7-9 weeks old mice were induced experimental periodontitis by inoculating the palatal gingival with 1x109 colony forming units of Aa. Mice were sacrificed 50 days later and intact maxilla harvested. The degree of alveolar bone loss was determined by micro-CT. Single suspensions of the epithelial cells isolated from palatal gingival tissues were assessed for the expressions of TLR-2 and TLR-4 proteins by flow cytometry and for TLR-2 and TLR-4 mRNA by reverse transcriptase PCR. Differences between the control and the disease groups were determined by students't- test. Results: Both TLR-2 and TLR-4 proteins were significantly elevated in the GEC of mice infected with A. actinomycetemcomitans when compared to the control group. The ratio of TLR-4 to TLR-2 mRNA was upregulated in chornic periodontitis as compared with the control group. Conclusion: Our data suggest that TLR-2 and TLR-4 are regulated differentially in A. actinomycetemcomitans-induced periodontitis.